Politeness Concepts in “Face to Face with Desi Anwar” on Metro TV: Pragmatic Perspective: Konsep Sopan santun dalam “Tatap Muka Desi Anwar” di Metro TV: Perspektif Pragmatis - Ihsan, Mas Darul (JEES (Journal of English Educators Society), 2019)
This research is to reveal the politeness strategies and intonation used by Desi and Dalai Lama. It is a qualitative research from the recorded interview of the TV program then transcribed into a text. The data triangulation and peer review are used. First, wants to invite Dalai Lama to search for an interpretation of the possible relevance through her hints. She delivers the information in a focus and it is based on context in the issues of a religious harmony. The utterances are supported by not only a manner expression such as raised eyebrow, puckered brow and shoulder bent forward, but also the intonation in a falling-rising tone. Second, Dalai Lama wants to be optimistic and centers his wants of creating a religious harmony to be unimpeded. The utterances are supported by not only a manner expression such as having a deep breathy voice and shaking his body, showing his finger up and down, but also the intonation in a falling tone. The findings imply that to achieve a mutual understanding in communication, someone should avoid the great mismatch in communication in addition to meet the purposes of communication, have a sense of awareness, and etiquette in the arena of language usage.